Food Security Improvement Policy in Urban Area Through Urban Farming Program in Malang (Studies in the Department of Agriculture and Food Security Malang) - Said Nasuiton; Asep Nurjaman (Universitas Muhammadiyah Malang, 2020)
Food security is inseparable from the factors of availability, quality, and affordability of food, where a country can assure the food needs of society ranging from families to individuals. This is mentioned in the latest Law number 18 of 2012 on Food, which states that food security includes the availability of food in quantity, quality, and affordability that aim to create a healthy, productive, and sustainable life. This paper discusses the extent to which the urban farming program as one of the government programs influences the community to achieve food security, especially family food needs. This research was conducted in several villages in five sub-districts of Malang, namely Klojen, Suku, Lowokwaru, Blimbing, and Kedungkandang. The research method used in this paper is qualitative descriptive. The primary data were collected through interviews and field observations, while the secondary data were collected through literature and documentation study. From the research conducted, the results show that this urban farming program influences several points about food security, especially those mentioned in Law number 18 of 2012, including availability, quality, and affordability. In addition, the research revealed that some locations are less able to develop urban farming programs effectively, due to the lack of supervision, socialization, and technical guidance.